Michigan Manual of Plastic Surgery. - Brown, David L. (Lippincott Manual Series., 2004)
The Michigan Manual of Plastic Surgery is the first and only pocket-sized, practical manual on plastic surgery. It is written by residents in the University of Michigan's world-renowned plastic surgery training program, with contributions from senior residents in related fields including general surgery, oral and maxillofacial surgery, otolaryngology, orthopaedics, neurosurgery, and urology. In an easy-to-follow outline format, the book covers the full range of clinical problems a plastic surgeon encounters. Sections cover fundamental principles and techniques, skin and soft tissue lesions, he.